Effect of Leverage, Firm Size, Institutional Ownership, and Profitability on CSR Disclosure in Consumer Goods Companies in Indonesia - Yudhistira Ardana; Fikri Rizki Utama; Audy Anzany Risvana (JFBA: Journal of Financial and Behavioural Accounting, 2023)
When investing in a company, investors frequently consider a number of criteria, such as financial success, brand or reputation, track record, and social effect through corporate social responsibility (CSR). This study seeks to quantify the impact of profitability, leverage, business size, and institutional ownership on the disclosure of corporate social responsibility. This study's sample is comprised of consumer products firms listed on the Indonesia Stock Exchange for the period of 2018–2020. The error correction model is the methodology utilized in this investigation. The long-term effects of leverage and business size on CSR disclosure were unfavorable and significant, according to the findings. The institutional ownership variable has a positive but not statistically significant effect, but the profitability variable has a statistically significant positive effect. On the other hand, the leverage variable has a substantial negative effect on CSR disclosure in the short term. While the scale of the organization has no negative influence of any significance, The influence of the institutional ownership variable is positive but insignificant. The profitability variable has a substantial beneficial impact.